Low and disparate seroprotection after pentavalent childhood vaccination in the Lao People's Democratic Republic: a cross-sectional study. (March 2017) - Evdokimov, K.; Sayasinh, K.; Nouanthong, P.; Vilivong, K.; Samountry, B.; Phonekeo, D.; Strobel, M.; Haegeman, F.; Heimann, P.; Muller, C.P.; Black, A.P.
Abstract: Objective: In Lao People's Democratic Republic, the high burden of vaccine-preventable diseases is thought to be mainly due to low vaccine coverage. We investigated the seroprotective response against diphtheria–tetanus–whole cell pertussis–hepatitis B– Haemophilus influenzae type b (DTPw-HepB-Hib) vaccine in children. Methods: Serum was collected from 1131 children aged 9 to 50 months and their mothers in a cross-sectional study between December 2013 and July 2014. All children had records of three injections of the DTPw-HepB-Hib vaccine. Serum was analysed for hepatitis B surface antigen (HBsAg), anti-HBsAg (anti-HBs), anti–hepatitis B virus core antigen (anti-HBc), anti-diphtheria and anti-tetanus antibodies. Stool samples were collected for detection of parasites. Demographic and nutritional information were also obtained. Results: Protective levels of anti-HBs antibodies were found in 394 (37.9%) of 1039 children; 529 (55.7%) of 950 and 809 (85.2%) of 950 children were seroprotected against diphtheria and tetanus. Time since vaccination, age, home birth and malnutrition only partially explained the poor vaccine responses. Overall, 81 (7.8%) of 1039 children and 445 (40.3%) of 1105 of mothers were anti-HBc positive. Ten (1.0%) of 1039 of the children and 77 (7.0%) of 1105 of the mothers were HBsAg carriers. Conclusions: After a full documented course of vaccination, seroprotective rates were unusually low and disparate against components of the pentavalent vaccine. These can only partially be explained by the negative predictors identified. Although many children had been infected, only few were chronic carriers of HBsAg. Our study demonstrates an urgent need to monitor the serologic response to vaccination, particularly in resource-poor countries.